Pengaruh Implementasi Shalat Dhuha Terhadap Kecerdasan Spiritual Siswa - Hertoni Hertoni (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2021)
According to many people, the dhuha sunnah prayer is useful for asking for the breadth of sustenance, which turns out to be not only in the form of material sustenance, but also sustenance that has an influence on spirituality and psychology related to spiritual intelligence (SQ) and personality that is very much dreamed of by education today for provide a solution to the moral decline of this nation. The data collection technique uses a questionnaire that has been tried out to be tested for validity and reliability. While the technical analysis of the data used is a simple product moment correlation statistical analysis technique which is then tested for hypotheses using a significant product moment correlation test which is consulted with a table at a significant level of 5% and 1% to provide an interpretation that the alternative hypothesis is accepted or rejected. And the comparative analysis of the effect of the implementation of the dhuha prayer on students' spiritual intelligence is by using a regression test. The results of this study indicate that there is a positive and significant relationship between the effect of the implementation of the dhuha prayer on the spiritual intelligence of the 5th and 6th graders of SDIT An-Nuur Purwosari Bojonegoro in the 2021/2022 academic year.